Financing and marketing strategies of selected farmers in the Province of Capiz - Castillo, Josephine Venus D (Iloilo City U.P. in the Visayas, 2007)
This study was conducted to determine the factors that caused the decline in volume of palay procurement of NFA-Capiz which resulted in the importation of rice from countries like Thailand and Vietnam. With the end view of addressing this concern, this study focuses on the financial and marketing strategies of farmer respondents and their perception of NPA's role in addrssng their marketing needs. A total of 116 farmer/members from various farmers' organizations from four municipalities in the province of Capiz were interviewed. Tabulated research findings were generated using SPSS and data was analyzed using descriptive statistics.Result show that most of the farmer respondents belong to the poor sector of society with income below the poverty line. Their economic status has much influence in themarketing f their farm produce or palay and their preference as to where to sell it. Since they could hardly finance their production expenses, they usually seek assistance from relatives,friends, individual money lenders/financing institutions, cooperatives and government support programs. Despite the fact that all of them rely on their cooperatives for their financial needs, some of them resort to borrowing money from private individuals through the "alili" system both for their farmng needs and daily sustenance. Being indebted to some individuals they could not sell their palay to any other buyerGiven the three marketing channels to choose from, their most preferred option is to sell their palay to local traders for convenience. Despite certain reqquirements, the farmers' second preference is the NFA because of its accessibility (through the mobile/buying station program and incentives.
"Final report (Research Methods in Management)"